Compulsory medical intervention versus external constraint in pandemic control - Douglas, T; Forsberg, L; Pugh, J (BMJ Publishing Group, 2020)
Would compulsory treatment or vaccination for Covid-19 be justified? In England, there would be significant legal barriers to it. However, we offer a conditional ethical argument in favour of allowing compulsory treatment and vaccination, drawing on an ethical comparison with external constraints—such as quarantine, isolation and ‘lockdown’—that have already been authorised to control the pandemic. We argue that, if the permissive English approach to external constraints for Covid-19 has been justified, then there is a case for a similarly permissive approach to compulsory medical interventions.